Shexiang Baoxin Pills for Coronary Heart Disease in Animal Models: Preclinical Evidence and Promoting Angiogenesis Mechanism - Zhang, Ke-Jian; Zhu, Jia-Zhen; Bao, Xiao-Yi; Zheng, Qun; Zheng, Guo-qing; Wang, Yan (Frontiers in Pharmacology, 2017)
Shexiang Baoxin Pill (SBP) originated from a classical TCM Fufang Suhexiang Pill for chest pain with dyspnea in the Southern Song Dynasty (1107-110 AD) and currently is still widely used for treating cardiovascular disease. Here, we aimed to evaluate preclinical evidence and possible mechanism of SBP for experimental coronary heart disease (CHD). Studies of SBP in animal models with CHD were identified from 6 databases until April 2016. Study quality for each included article was evaluated according to the CAMARADES 10-item checklist. Outcome measures were myocardial infarction area, vascular endothelial growth factor (VEGF) and microvessel count (MVC). All the data were analyzed by using RevMan 5.1 software. As a consequence, 25 studies with 439 animals were identified. The quality score of studies ranged from 2 to 5, with the median of 3.6. Meta-analysis of 7 studies showed more significant effects of SBP on the reduction of the myocardial infarction area than the control (P<0.01). Meta-analysis of studies showed significant effects of SBP for increasing VEGF expression compared with the control (P<0.01). Meta-analysis of 10 studies indicated that SBP significantly improved MVC compared with the control (P<0.01). In conclusion, these findings preliminarily demonstrated that SBP can reduce myocardial infarction area, exerting cardioprotective function largely through promoting angiogenesis.